Ketoprak story of Sultan Agung Tani as a cultural means of resolving inter-subethnic conflicts in coastal and inland Java - Purnomo, Sucipto Hadi; Astuti, Eka Yuli; Widodo, Widodo; Yahaya, Samsur Rijal (Diksi, 2024)
The story of Sultan Agung Tani becomes a means of resolving cultural conflicts in Java between inland and coastal subcultures. In Java, the legacy of cultural conflict has never been completely resolved until now due to the impact of the legacy of colonialism that has persisted since the arrival of the VOC in the 17th century. This story was chosen because it depicts the conflict and resolution between two Javanese subethnic groups who have significant differences in culture, values and geographical background. The hermeneutic reading method with a postcolonial approach is used to analyze the story of Sultan Agung Tani which is recorded in audio and video format. The results of this research show that the pattern of conflict resolution between Javanese sub-ethnic groups through stories of Ketoprak performances is able to influence people's cultural mindset. Ketoprak stories that narrate the resolution of Javanese inter-subethnic conflicts, which are staged by Ketoprak groups in coastal areas, especially Pati Regency in Central Java and its surroundings, have a positive social impact on coastal communities who are depicted as inferior by narrative text stories from the interior in babad stories. Through the stories presented, the potential to provide a cultural model of conflict resolution contributes to a conflict resolution formula with dramatic steps provided to become a dish that is enjoyed. This research provides in-depth insight into how the traditional performing art of Ketoprak can act as an important tool in mediating conflict and promoting inter-subethnic reconciliation in Indonesia.